2020
DOI: 10.5194/acp-2020-753
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parameterizing the vertical downward dispersion of ship exhaust gas in the near-field

Abstract: Abstract. Estimating the impact of ship emissions on local air quality is a topic of high relevance, especially in large harbour cities. For chemistry transport modeling studies, the initial plume rise and dispersion play a crucial role for the distribution of pollutants into vertical model layers. This study aims at parameterizing the vertical downward dispersion in the near-field of a prototype cruise ship, depending on several meteorological and technical input parameters. By using the micro-scale transport… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…From analysis of transient particle events, wind data and ship transponder signals, it becomes apparent that accuracy in wind data, possible mixing of different plumes during high traffic and prevailing wind directions are key limiting factors rather than chemical detection limits or background air pollution. Consequently, SPMS-based monitoring systems should acquire local wind data and small-scale plume dispersion models should be integrated (Matthias et al, 2018;Badeke et al, 2020). The 435 possible operation time is mainly limited by the prevailing wind directions, which should be perpendicular to the ship lane to avoid plume mixing and straight to the monitoring site.…”
Section: Discussionmentioning
confidence: 99%
“…From analysis of transient particle events, wind data and ship transponder signals, it becomes apparent that accuracy in wind data, possible mixing of different plumes during high traffic and prevailing wind directions are key limiting factors rather than chemical detection limits or background air pollution. Consequently, SPMS-based monitoring systems should acquire local wind data and small-scale plume dispersion models should be integrated (Matthias et al, 2018;Badeke et al, 2020). The 435 possible operation time is mainly limited by the prevailing wind directions, which should be perpendicular to the ship lane to avoid plume mixing and straight to the monitoring site.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the dispersion on local or urban scales that also considers obstacle effects has recently been investigated using wind tunnels and CFD models (e.g. Badeke et al, 2020).…”
Section: Air Quality Modelling From Local To Regional Scalesmentioning
confidence: 99%
“…Recent micro-scale model simulations also showed the importance of barrier effects for emissions from large ships. It was thus shown that turbulence at the stern of the ship may cause a significant decrease in exhaust pollutants, leading to higher concentrations near the ground and, most likely, higher exposure of the nearby urban population (Badeke et al, 2020). The application of LES Wolf-Grosse et al, 2017;Resler et al, 2020;Werhahn et al, 2020;, Khan et al, 2020 and CFD (San José et al, 2020;Gao et al, 2018;Flageul et al, 2020;Koutsourakis et al, 2020;Nuterman et al, 2011;Buccolieri et al, 2020, Kurppa et al, 2018Kurppa et al, 2019;Karttunen et al, 2020;Kurppa et al, 2020) models for air quality assessment in urban environments is becoming a frequent approach.…”
Section: Improved Turbulence and Dynamics For Higher Resolution Assessment Of Urban Air Qualitymentioning
confidence: 99%